Bariatric Surgery in the United Kingdom: A Cohort Study of Weight Loss and Clinical Outcomes in Routine Clinical Care. - Ian J Douglas; Krishnan Bhaskaran; Rachel L Batterham; Liam Smeeth (PLoS Medicine)
Background Bariatric surgery is becoming a more widespread treatment for obesity. Comprehensive evidence of the long-term effects of contemporary surgery on a broad range of clinical outcomes in large populations treated in routine clinical practice is lacking. The objective of this study was to measure the association between bariatric surgery, weight, body mass index, and obesity-related co-morbidities. Methods and findings This was an observational retrospective cohort study using data from the United Kingdom Clinical Practice Research Datalink. All 3,882 patients registered in the database and with bariatric surgery on or before 31 December 2014 were included and matched by propensity score to 3,882 obese patients without surgery. The main outcome measures were change in weight and body mass index over 4 y; incident diagnoses of type 2 diabetes mellitus (T2DM), hypertension, angina, myocardial infarction (MI), stroke, fractures, obstructive sleep apnoea, and cancer; mortality; and resolution of hypertension and T2DM. Weight measures were available for 3,847 patients between 1 and 4 mo, 2,884 patients between 5 and 12 mo, and 2,258 patients between 13 and 48 mo post-procedure. Bariatric surgery patients exhibited rapid weight loss for the first four postoperative months, at a rate of 4.98 kg/mo (95% CI 4.88-5.08). Slower weight loss was sustained to the end of 4 y. Gastric bypass (6.56 kg/mo) and sleeve gastrectomy (6.29 kg/mo) were associated with greater initial weight reduction than gastric banding (2.77 kg/mo). Protective hazard ratios (HRs) were detected for bariatric surgery for incident T2DM, 0.68 (95% CI 0.55-0.83); hypertension, 0.35 (95% CI 0.27-0.45); angina, 0.59 (95% CI 0.40-0.87);MI, 0.28 (95% CI 0.10-0.74); and obstructive sleep apnoea, 0.55 (95% CI 0.40-0.87). Strong associations were found between bariatric surgery and the resolution of T2DM, with a HR of 9.29 (95% CI 6.84-12.62), and between bariatric surgery and the resolution of hypertension, with a HR of 5.64 (95% CI 2.65-11.99). No association was detected between bariatric surgery and fractures, cancer, or stroke. Effect estimates for mortality found no protective association with bariatric surgery overall, with a HR of 0.97 (95% CI 0.66-1.43). The data used were recorded for the management of patients in primary care and may be subject to inaccuracy, which would tend to lead to underestimates of true relative effect sizes. Conclusions Bariatric surgery as delivered in the UK healthcare system is associated with dramatic weight loss, sustained at least 4 y after surgery. This weight loss is accompanied by substantial improvements in pre-existing T2DM and hypertension, as well as a reduced risk of incident T2DM, hypertension, angina, MI, and obstructive sleep apnoea. Widening the availability of bariatric surgery could lead to substantial health benefits for many people who are morbidly obese.